KARYOTYPE STUDIES IN LYCIUM SECTIONS SCHISTOCALYX AND SCLEROCARPELLUM (SOLANACEAE) - STIEFKENS, L.; BERNARDELLO, G. (Edinburgh Journal of Botany, 2006)
Mitotic chromosome numbers and karyotypes of species in two sections of Lycium (Solanaceae) from the American continent were determined in 23 populations. Both species in the small South American section Schistocalyx were examined: Lycium ciliatum and three varieties of L. chilense had diploid (2n=24) as well as tetraploid (2n=48) populations. Lycium ameghinoi from the small American section Sclerocarpellum was diploid with 2n=24. The basic number x=12 for the genus was confirmed. The karyotypes of these taxa were highly symmetrical: the chromosomes were metacentric or submetacentric with the formula: 11 m + 1 sm. Microsatellites were present in chromosome pair no. 1 and were attached to the short arms. As in other Lycium taxa already investigated, karyotypic features suggest that morphological differentiation in the group has not been accompanied by karyotype divergence.